Paradoxical influence of family ownership on innovation-focused organizational change: Evidence from a large family business retail firm. Issue 4 (29th November 2019) - Szymanska, Izabela; Blanchard, Anita; Kuhns, Kaleigh
Abstract : Purpose: The purpose of this paper is to focus on efforts of a large department store to increase its business advantage by boosting innovation. The first broad research question of this study investigated how the family and non-family members influence the process of organizational change aimed at greater innovativeness in a successful retail family business. The second research question was how the family enterprise handles the tension between change stemming from innovation and progress and the need for stability continuity tradition and maintenance of family control. Design/methodology/approach: This study is an in-depth inductive analysis (Glaser and Strauss, 1967) of an important and unique case (Yin, 1994). Findings: The results of the study indicate that the push toward innovation was initiated by family members and that it was focused largely on creating structural support for the innovation activity keeping this activity tightly under monitoring and control by upper management. The attempts at equipping employees with innovation-relevant decision-making authority or consulting the clients in designing novel projects were absent, while the move to change the organizational culture was measured. Originality/value: This study makes several contributions to the academic literature. It offers an empirical assessment of the effects of emotional attachment and ownership concentration on innovation management, a phenomenon postulated by Kotlar et al. (2016). These two characteristics pulled innovation-boosting initiative in opposite directions creating a unique dynamics. This research also provides an example of organizational identity that hinders the innovation process in the context of a family business that survived and developed over generations.